Arquiz: serious game virtual para sensibilizar jovens quanto ao risco de uso de drogas - Fernandes, Anderson Mine (2016)
Adolescence is a stage of discovery and self-affirmation, commonly known by the concern of parents, this makes young people vulnerable to various problems, including drug use, which requires attention to these teenagers do not enter this world. The government is doing its part by distributing information leaflets and campaigns on the use of drugs, but usually these board not succeed by treating the youth as problematic and being a more traditional way can no longer attract attention and can be considered an inappropriate way for this public. On another side, young people have fascination for games. It is believed that an approach using electronic educational games can achieve greater success due to the attractive environment they offer. In studies conducted in young people, with common games and electronic games could be noted the importance of using this type of intervention. This work presents a proposal for development through a game with Augmented Reality as an aid strategy in information and prevention of drug use in young people and adolescents, a type of game where a technology was used to mix the real world with 3D images . The survey also conducted a metric for research within the school environment, which has the public necessary for the implementation of the game. Analyzing the results it can be concluded that the game featured potential for this community could make up a greater awareness than other approaches presented.